Our First Unisex President?: Black Masculinity and Obama's Feminine Side - Cooper, Frank Rudy (2009)
People often talk about the significance of Barack Obama's status as our first black President. During the 2008 Presidential campaign, however, a newspaper columnist declared, If Bill Clinton was once considered America's first black president, Obama may one day be viewed as our first woman president. That statement epitomized a large media discourse on Obama's femininity. In this essay, Professor Frank Rudy Cooper thus asks how Obama will influence people's understandings of the implications of both race and gender. To do so, he explicates and applies insights from the fields of identity performance theory, critical race theory, and masculinities studies. With respect to race, the essay confirms his prior theory of bipolar black masculinity. That is, the media tends to represent black men as either the completely threatening and race-affirming Bad Black Man or the completely comforting and assimilationist Good Black Man. For Obama, this meant he had to avoid the stereotype of the angry black man. Meanwhile, though, the association of the Presidency with the hegemonic form of masculinity presented difficulties for Obama. He was regularly called upon to be more aggressive in responding to attacks and more masculine in general. As a result, Obama could not be too masculine because that would have triggered the Bad Black Man stereotype but he could not be too feminine because that would have looked unpresidential. Obama solved that dilemma by adopting a unisex style. He was a candidate who was designed to be suitable to either gender. Professor Cooper believes Obama's unisex performance on the world's biggest stage suggests that we are all more free to perform our race and our gender as we see fit than we had previously believed